Optimisation and scale-up of production of biodegradable polymer in stirred tank fermentation - Nafsiah, Hussain; Rosmerah, Liaw; Goh, Mei Fong; Azrina, Mat Isa; Jailani, Salihon (2008)
Polyhydroxybutyrates (PHB) are natural, biodegradable polymers which are accumulated as an energy reserve material by a large number of bacteria when nutrient such as nitrogen source is available in limiting concentrations in the present of excess carbon source. The major problem associated with the industrial production of PHB is its high production cost. In the present study, effort was made to screen out the variables that influence the production of biomass and PHB by the bacteria Cupriavidus necator in shake-flask fermentations using the method of Factor Analysis. The variables studied are the concentrations of glucose, CaCI2.2H20, trace element, (NH4)2S04 and Na2HP04.7H20, and agitation and temperature. The levels of variables that were found to have significant influence on the production of biomass and PHB were then optimized in shake-flask fermentations using the methods of factorial experiments and composite design. The optimized shake-flask fermentation was then scaled-up to 1OL stirred tank fermentation using the method of constant volumetric mass transfer coefficient of oxygen (kLa) at both scales. The ha value was derived by fitting the mass transfer equation to the data of dissolved oxygen concentration [ which was derived from the data of dissolved oxygen tension (DOT)] versus time on computer using the Simplex Method on Matlab with two unknowns, namely kLa and the electrode mass transfer coefficient (kap) of oxygen. The stirrer speed (rpm) and the air flow rate (A) in the 1OL fermentor that produced the same value of kLa found in the optimized conditions in shake-flask was approximated by trial and error.